Allocating Marine Expeditionary Unit Equipment and Personnel to Minimize Shortfalls Second Edition - Perry, Walter L. (RAND Corporation, 2013)
In many cases, the available space on a Marine Expeditionary Unit's (MEU's) ships falls far short of what is needed to transport the full set of required equipment. A RAND-developed software tool, the Marine Air-Ground Task Force (MAGTF) Equipment Structural Assessment (MESA) application, was designed to assist MEU mission planners in maximizing the effectiveness of limited equipment inventories.